Interaction between SO2 and NO in their adsorption and photocatalytic conversion on TiO2. (June 2020) - Wang, Haiming; Liu, Hanzi; Chen, Zhen; Veksha, Andrei; Lisak, Grzegorz; You, Changfu
Abstract: The simultaneous adsorption and photocatalytic conversion of SO2 and NO on P25–TiO2 were studied. In particular, the interaction of SO2 and NO on each other's adsorption and photocatalytic oxidation was discussed. The adsorption of NO on P25 was negligible when comparing to that of SO2, while with the coexistence of NO and SO2 in flue gas, both the adsorption of SO2 and NO were improved. In the presence of water and oxygen, the photocatalytic oxidation efficiency of NO with an efficiency of >69% was observed on irradiated TiO2 surface, which lasted for at least 1000 min. Oxygen was found to have much more important effect than water on the photocatalytic oxidation of NO. In the presence of SO2 however, the photocatalytic process of NO was largely reshaped. The whole process was controlled by the photocatalytic oxidation of SO2 . A dramatic efficiency decease (breakthrough of the catalyst bed) was observed for both NO and SO2 due to the catalyst deactivation caused by the poisoning of SO2 oxidation products. Before the breakthrough, the photocatalytic conversion efficiency of NO increased with increasing the SO2 concentration, which was mainly due to the improved NO adsorption in the presence of SO2 . Highlights: Co-existence of NO and SO2 improved adsorption of each other on P25–TiO2 surface. O2 played a more important role than H2 O in the photocatalytic conversion of NO. The photocatalysis of NO became ineffective in the presence of SO2 . Removal process was controlled by the catalyst deactivation due to sulfur poison.